2005
DOI: 10.1556/avet.53.2005.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Borrelia burgdorferi genospecies inducing Lyme disease in dogs from Western Poland

Abstract: Canine Lyme borreliosis may be caused by three Borrelia burgdorferi sensu lato genospecies. The prevalence of infection by Borrelia species was determined by nested polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP) with the enzyme Fsp4H I in the blood of dogs naturally infested by ticks in an endemic region of Poland. Blood samples were collected from 98 dogs of various breeds, delivered to the Veterinary Clinic in Szczecin (northwestern Poland) for various reasons. Nested PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
(15 reference statements)
0
15
0
Order By: Relevance
“…Most human cases of borreliosis were originally recorded in the north-eastern part of the country, but there have since also been reports of the pathogen from the north-western region in ticks (Skotarczak et al 2002, 2003; Skotarczak 2000; Wodecka and Skotarczak 2000) and of pathogen DNA also in dogs (Skotarczak and Wodecka 2003, 2005). One study from Poland furthermore confirmed the role of the genospecies B. burgdorferi s.s. in canine borreliosis (Wodecka et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most human cases of borreliosis were originally recorded in the north-eastern part of the country, but there have since also been reports of the pathogen from the north-western region in ticks (Skotarczak et al 2002, 2003; Skotarczak 2000; Wodecka and Skotarczak 2000) and of pathogen DNA also in dogs (Skotarczak and Wodecka 2003, 2005). One study from Poland furthermore confirmed the role of the genospecies B. burgdorferi s.s. in canine borreliosis (Wodecka et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies on ticks and forest workers in the north-western part of the country revealed prevalences between 7.4 % (Skotarczak et al 2002) and 16.7 % (Skotarczak et al 2003) in the tick population and 61 % in forest workers (Niścigorska et al 2003). Seropositivity was also recorded in dogs in the north-western part of Poland (Skotarczak and Wodecka 2003, 2005). The main vector in the area for the pathogen B. burgdorferi s.l.…”
Section: Introductionmentioning
confidence: 97%
“…In north-west Poland B burgdorferi sensu stricto DNA was detected in 163 per cent of blood samples from dogs (Skotarczak and Wodecka 2005). The results of this study differ from those from north-west Poland, but it is not possible to compare the results owing to transient spirochaetaemia (Aguero-Rosenfeld and others 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Borrelia seropositivity is common amongst dogs because many of them carry a persistent infection for life and only a fraction of infected animals (~5%) enters the disease status (Beugnet 2002). Borrelia afzelii, B. burgdorferi sensu stricto and Borrelia garinii are found commonly in European dogs (Speck et al 2001, Skotorczak andWodecka 2005), and mixed infection with four species (B. burgdorferi s.s., B. afzelii, B. garinii and Borrelia valaisiana) may also occur (Hovius et al 1998). The pathogenic significance of the above-mentioned European Borrelia spp.…”
Section: Lyme Borreliosis Is Caused By Tick-transmittedmentioning
confidence: 99%